Rescheduling Part 2 of the 11+ reduces injury burden and increases compliance in semi-professional football - Whalan, M.; Lovell, R.; Steele, J. R.; Sampson, J. A. (Scandinavian Journal of Medicine & Science in Sports, 2019)
Although the 11+ programme has been shown to reduce injuries in sub-elite football, programme compliance is typically poor, suggesting that strategies to optimize delivery are necessary. This study investigated the effect of rescheduling Part 2 of the three-part 11+ programme on programme effectiveness. Twenty-five semi-professional football clubs were randomly allocated to either a Standard-11+ (n=398 players) or P2post group (n=408 players). Both groups performed the 11+ programme at least twice a week throughout the 2017 football season. The Standard-11+ group performed the entire 11+ programme before training activities commenced, whereas the P2post group performed Parts 1 and 3 of the 11+ programme before and Part 2 after training. Injuries, exposure and individual player 11+ dose were monitored throughout the season. No significant between group difference in injury incidence rate (P2post vs Standard-11+ = 11.8 vs 12.3 injuries/1000 h) was observed. Severe time loss injuries >28 days (33 vs 58 injuries; p<0.002) and total days lost to injury (4303 vs 5815 days; p<0.001) were lower in the P2post group. A higher 11+ programme dose was observed in the P2post (29.1 doses; 95% CI 27.9-30.1) versus Standard-11+ group (18.9 doses; 95% CI 17.6 -20.2; p<0.001). In semi-professional football, rescheduling Part 2 of the 11+ programme to the end of training maintained the effectiveness of the original 11+ programme to reduce injury incidence. Importantly, rescheduling Part 2 improved player compliance and reduced the number of severe injuries and total injury burden thereby enhancing effectiveness of the 11+ programme.